Alias. The complete fifth season [videorecording (DVD)] - Garner, Jennifer, 1972-; Vartan, Michael; Rifkin, Ron; Garber, Victor; Abrams, J. J. (Jeffrey Jacob), 1966- (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Secret agent Sydney Bristow returns to settle the score once and for all. Experience the stunning action as Sydney discovers that she is pregnant with Agent Vaughn's baby, and tragedy strikes before he can reveal more about his secret past.